(untitled) (The Pretoria Student Law Review, 2023)
This article is inspired by a need to clarify and appraise the law relating to the sale of goods with particular attention to the market overt principle in Zambia. This will be done by conducting a comparative study between Zambia, South Africa, and Nigeria. The article investigates methods for constructing a preferable legal regime for individuals and businesses, particularly economic transactions. It further assesses the Zambian Sale of Goods Act of 1893 (56 & 57 Vict. c.71) as it relates to the market overt principle. I also highlight weaknesses in the current law requiring remedial action.